Biodemulsifiers produced by Achromobacter sp. and their features in improving the biodegradation of phenanthrene. Issue 8 (16th January 2017) - Li, Chunyan; Jia, Tingting; Fu, Meng; Hou, Ning; Cao, Huiming; Wang, Qiaoruo; Li, Dapeng
Abstract : The application of biodemulsifiers plays an essential role in oil recovery and demulsification. Abstract : The application of biodemulsifiers plays an essential role in oil recovery and demulsification. However, little is known about their features during the biodegradation of petroleum hydrocarbons. In the present study, a demulsifying strain of Achromobacter sp. LH-1 was applied for the degradation of petroleum hydrocarbons and the effects of the biodemulsifiers produced by LH-1 during the degradation process were investigated. Several common petroleum hydrocarbons, including aromatic and aliphatic compounds, were utilized by strain LH-1 as the sole carbon source for the production of biodemulsifiers. Taking phenanthrene (PHE) as the sole carbon source with an initial concentration of 100 mg L −1, the optimal cultivation conditions were determined using response surface methodology based on a Box–Behnken design to further enhance demulsification efficiency. The results showed that LH-1 could secret lipopeptide extracellular biodemulsifiers and achieved 95.6% demulsification efficiency for water-in-oil model emulsions within 24 h and 92.3% PHE degradation efficiency within five days. It demonstrated that biodemulsifier-induced dissolution played the dominant role in PHE degradation and thus, the excellent PHE degradation capability of LH-1 is closely related to biodemulsifier production.